Cost Efficiency of the Egyptian Banking Sector: A Panel Data Analysis - Hassan, Hassan Ismail; Jreisat, Ammar (International Journal of Economics and Financial Issues, 2016)
Based on a two stage method this paper investigates the determinants of the cost efficiency of Egyptian banking sector. Employing Data Envelopment Analysis (DEA). we compare the cost efficiency of large, medium and small banks and the cost efficiency of foreign and domestic banks using a balanced panel which cover 14 banks operating in Egypt from 1997 to 2013. In the first stage, cost efficiency scores are computed using an input-oriented data envelopment analysis (DEA). At the second stage, cost efficiency scores are regressed on a set of potential explanatory variables in a logit model. While the cost efficiency scores show large improvements in the early and third phases of financial deregulation. Over the entire sample period, cost efficiency has declined at the rate of 0.963% per annum. Our finding indicates that age, loan to net interest margin, return on equity and good management practises positively affects banks cost efficiency and number of bank branches negatively affects bank cost efficiency. Keywords: Cost Efficiency, Two-stage Data Envelopment Analysis, Egyptian Banks. JEL Classifications: D22, D24, D61, G21